An investigation of the link between major shareholders' behavior and corporate governance performance before and after the COVID-19 pandemic: A case study of the companies listed on the Iranian stock market - Rezvan Pourmansouri; Amir Hedayati Mehdiabadi; Vahid Shahabi; Cristi Spulbăr; Ramona Birau (Journal of Risk and Financial Management, 2022)
One of the basic functions of establishing corporate governance (CG) in companies is improving performance and increasing value for shareholders. Expanding the company's value will ultimately increase the shareholders' wealth. Therefore, it is natural for shareholders to seek to improve their performance and increase the company's value. If CG mechanisms cannot perform this function in companies, they do not have the necessary efficiency and effectiveness and, therefore, cannot improve the efficiency of companies. This article investigated the connection between the power of major shareholders and the modality of CG of companies listed on the Iranian capital market before and after the COVID-19 pandemic. The statistical sample of the research included 120 companies listed on the Tehran Stock Exchange for the selected period from 2011 to 2021. The results showed that the concentration of ownership is harmful to adopting corporate governance (GCG) practices. In particular, the high level of voter ownership concentration weakens the corporate governance system (CGS). The results of this study, which was conducted using panel analysis, revealed that the concentration of ownership impairs the quality of CGS, and major shareholders cannot challenge the power of the main shareholder; it alsonegatively affected the quality of business boards, both during and before the COVID-19 pandemic. The competitiveness and voting rights of the major shareholders negatively affected the quality of board composition before and after the COVID-19 pandemic. The concentration of voter ownership also negatively affected the quality of CGS, both during and before COVID-19, and the competitiveness and voting rights of major shareholders before COVID-19. This concentration positively affected the quality of CGS after the COVID-19 pandemic.
Keywords: 650; COVID-19 pandemic; corporate governance; agency theory; emerging economy; financial management; global economy; Iran; ownership concentration